Physical treatment of posttraumatic elbow contractures in children – our experience - Gocevska, Marija; Nikolikj Dimitrova, Erieta; Koevska, Valentina; Mitrevska, Biljana; GJerakaroska Savevska, Cvetanka; Kalchovska, Biljana; Manoleva, Maja; Todorovikj, Lazar (Scientific Foundation SPIROSKI, 2022)
The most common complications of elbow trauma are contractures and neurovascular injuries. The complications can be a result of the initial injury, but they can also be a result of a surgical treatment. In addition to orthopedic treatment of elbow fractures, physical therapy and rehabilitation play a significant role in treatment of posttraumatic contractures. To determine the effects of physical therapy and rehabilitation of posttraumatic elbow contractures in children. This was a retrospective cross-sectional study conducted in the University Clinic for Physical Medicine and Rehabilitation, Skopje in the period 01.01.2021 – 01.07.2022. A total of 52 children were included, at the age between 2 and 13 years who had a posttraumatic elbow contracture, limited range of motion, pain and/or limitations in accomplishing daily activities. Depending on the clinical finding, children underwent a relevant physical therapy (kinesitherapy, functional therapy, electrotherapy, thermotherapy, hydrotherapy and magnetotherapy) in duration of three weeks. For assessing the effects of the rehabilitation therapy, the range of motion of the elbow and forearm was examined along with the Flynn’s scale in all children, prior to and after completion of the physical treatment. Applied physical treatment resulted in a significant improvement in all analyzed movements such as: elbow flexion (p=0.00001), elbow extension (p=0.00001), forearm pronation (p=0.00001), forearm supination (p=0.0000) and Flynn’s scale (p=0.0000). After completion of the rehabilitation treatment, excellent results were registered in 41 (85%) children, moderate in 10 (19.23%) and favorable in 1 (1.92%). Timely and adequate application of physical therapy and rehabilitation can significantly improve the final outcome in treatment of posttraumatic elbow contractures in children. A combination of different physical procedures adequately applied and personalized can significantly improve the range of motion of the elbow.
Keywords: rehabilitation; contracture; elbow; children; fracture